2007
DOI: 10.1089/end.2006.0194
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Pyelovesical Bypass As Replacement for Standard Percutaneous Nephrostomy for Palliative Urinary Diversion: Prospective Evaluation of Patient's Quality of Life

Abstract: The subcutaneous pyelovesical bypass provides a better quality of life than a standard percutaneous nephrostomy tube in terminally ill patients by making them external-tube free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Investigators have found no dislodgment or encrustation of the diversion tube. Moreover, there may be significant improvement in patients' quality of life (QOL) after placement [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have found no dislodgment or encrustation of the diversion tube. Moreover, there may be significant improvement in patients' quality of life (QOL) after placement [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…A prospective evaluation of their patients' quality using the EORTC QLC-30 questionnaire following insertion of the Detour EAS demonstrated an improvement of the function scale as a result of the elimination of the external percutaneous tube and a parallel worsening of the symptom scale secondary to the progression of disease (http://groups.eortc.be/qol/ questionnaires_qlqc30.htm). Patient ratings of the global quality of life and satisfaction with the urinary diversion were high because of the absence of the percutaneous tube (Desgrandchamps et al, 2007). Other authors have since reported equally excellent results with the Detour EAS (Lloyd et al, 2007;Olsburgh et al, 2007;Burgos et al, 2009).…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…Moreover, the investigators found a significant improvement in patient QOL, as measured by the validated European Organization for the Research and Treatment of Cancer QLQ-C30 scale, After PCN removal and nephro-vesical bypass placement up to 18 months after the procedure. Patients were able to void normally, which can also have significant impact on QOL compared to that with indwelling Foley catheters or wearing diapers at the end of life [22]. In another study, in five patients (17.9%) of 31, the system had to be replaced due to occlusion at a mean follow-up of 10.2 months [23].…”
Section: Discussionmentioning
confidence: 99%